KEPENTINGAN KOTA PADANG MENJALIN KERJASAMA DENGAN INDIAN OCEAN RIM ASSOCIATION (IORA) - Aulia Safitri; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of the study was to find a general description of IORA, to provide information about the optimization of the city of Padang and the collaboration between the city of Padang and IORA. This thesis theory is paradiplomasi referring to international relations carried out sub-national, regional, local agencies, for their interests. subnational government (SNG) or regional government There are several supporting factors that explain gaining its place in the world of international relations, first, namely the development of actors in international relations as a result of globalization. Secondly, although SNG's role has become increasingly significant, it is not labeled as a development that only attracts media attention.This study applies a qualitative method by collecting data from various references. Through books and scientific journals, the authors analyze by looking for the same themes as the writing of the research being carried out then taking the core of matters relating to research. The city of Padang was involved as host of a meeting of the Indian Ocean Rim Association (IORA).In this study the IORA will be analyzed will be explained using the concept of subnational government, through several factors, such as infrastructure, GDP, labor and others. Data analysis will then begin by identifying what potential the City of Padang has. Opportunities are opened to promote the potentials of the City of Padang to IORA member countries which then open up investment and cooperation opportunities between the Padang City government and IORA member countries. In addition, the city of Padang is also a city that is believed to be able to carry out international events.Keywords: Interests, City of Padang, IORA, Cooperation, Regional.